Effect of Profitability, Business Risk, and Intellectual Capital on Company Value - Utomo, Teguh; Simanungkalit, Royhisar Martahan (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to partially determine the effect of profitability, business risk and intellectual capital on company value. The study population was determined through the annual reports of property & real estate sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period, totaling 93 companies. The study samples were selected using purposive sampling technique, in this case only selecting companies that consistently issued annual reports along with profit performance during the study period, which obtained 13 companies. The data analyzed here were secondary data. Regarding variable assessment, company value referred to the Price Book Value (PBV) proxy and profitability referred to the Return on Assets (ROA) proxy which was calculated by dividing net profit by total assets as a measure of profitability ratio. In addition, business risk referred to the proxy of natural logarithm of the standard deviation of Earnings Before Interest and Taxes (EBIT) and intellectual capital referred to the Value Added Intellectual Capital (VAIC) proxy which was calculated using the Value Added of Capital Employed (VACA) plus the Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA). Data were analysed through descriptive analysis and panel data regression analysis techniques using the Eviews software. The study results revealed that profitability had a positive effect on company value. In contrast, business risk and intellectual capital had no effect on company value.